2021
DOI: 10.1111/raq.12633
|View full text |Cite
|
Sign up to set email alerts
|

Autogenous vaccination in aquaculture: A locally enabled solution towards reduction of the global antimicrobial resistance problem

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 100 publications
0
30
0
1
Order By: Relevance
“…Autogenous vaccines provide an emergency solution for combating insidious pathogens and has been proposed to control P. salmonis . These are vaccines produced from pathogens directly isolated from the affected farms, in which the elaborated vaccines can be implemented at lower frequencies and with more control ( 119 , 120 ). The benefits of this type of vaccine are its effectiveness against local serotypes of variable pathogens and its ability to be rapidly reformulated compared to regular commercial vaccines ( 119 , 121 ).…”
Section: How To Avoid Vaccines Fail Against Piscirickettsiosismentioning
confidence: 99%
See 1 more Smart Citation
“…Autogenous vaccines provide an emergency solution for combating insidious pathogens and has been proposed to control P. salmonis . These are vaccines produced from pathogens directly isolated from the affected farms, in which the elaborated vaccines can be implemented at lower frequencies and with more control ( 119 , 120 ). The benefits of this type of vaccine are its effectiveness against local serotypes of variable pathogens and its ability to be rapidly reformulated compared to regular commercial vaccines ( 119 , 121 ).…”
Section: How To Avoid Vaccines Fail Against Piscirickettsiosismentioning
confidence: 99%
“…These are vaccines produced from pathogens directly isolated from the affected farms, in which the elaborated vaccines can be implemented at lower frequencies and with more control ( 119 , 120 ). The benefits of this type of vaccine are its effectiveness against local serotypes of variable pathogens and its ability to be rapidly reformulated compared to regular commercial vaccines ( 119 , 121 ). Additionally, autogenous vaccines can control outbreaks and decrease the use of antimicrobials ( 119 ).…”
Section: How To Avoid Vaccines Fail Against Piscirickettsiosismentioning
confidence: 99%
“…Use of antibiotics and chemotherapies that were historically used to mitigate such disease outbreaks has rapidly declined in recent years and is now banned in many countries due to the development of antimicrobial resistance [5,6]. This decreased use of antibiotics has coincided with increased research efforts to develop novel antimicrobial therapies including vaccines [7,8], probiotics [9], medicinal plants [10] and antimicrobial compounds [5].…”
Section: Introductionmentioning
confidence: 99%
“…To maintain the fish health and/or to control disease outbreaks, antibiotics have at least to some extent been applied in aquaculture, which has caused wide concerns over food safety of aquaculture products, and also resulted in antimicrobial resistance of pathogenic bacteria and viruses 3 . Barnes et al, 3 in their review article, propose to develop autogenous vaccination to combat antimicrobial resistance in aquaculture 3 . Autogenous vaccines are defined as custom vaccines produced from pathogens isolated directly from affected farms, and used locally in these farms.…”
mentioning
confidence: 99%
“…Barnes et al 3 analyse the pathway towards the success of vaccine application in salmon production in Norway in comparison with the antibiotic use in Chile also in salmon production. They further examine cultured species diversity, diseases, pathogen genetic variations in a few countries, such as Indonesia, Vietnam and Thailand, and concluded that autogenous vaccines have advantages in many low‐ and middle‐income countries in terms of intellectual property, efficacy and flexibility.…”
mentioning
confidence: 99%